PERLINDUNGAN HAK PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Yusfiana Naja (Jurnal Hukum Cassowary, 2025)
Domestic Violence (DV) is a legal and social problem that continues to affect many women in Indonesia, in the form of physical, psychological, sexual violence, and economic neglect. This article aims to analyze and compare how Islamic law and Indonesian positive law, specifically Law Number 23 of 2004 concerning the Elimination of Domestic Violence, provide protection for the rights of women as victims of domestic violence. This research uses a normative juridical method with a library research approach, a legislative approach, and a comparative approach, which examines primary legal materials in the form of the Qur'an, hadith, and laws and regulations, as well as secondary legal materials in the form of books, scientific journals, and previous research results. The results of the study indicate that Islamic law through the principle of maqashid sharia places the protection of women's lives, honor, and offspring as a fundamental goal of sharia, while Indonesian positive law regulates such protection through more operational criminal, civil, and administrative procedural mechanisms. These two legal systems have a common ground in the spirit of protecting victims, although they differ in their epistemological basis and enforcement instruments, so that harmonization of gender justice values ​​from both perspectives is necessary.